Miniature micro hydro power center to improve critical thinking skills for elementary school students - Purwandari, Ristiana Dyah; Putrianasari, Desi; Mulyadi, Abdul Haris; Al-Kharis, Vina Zahra; Alkharis, Vira Zahra (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2026)
The Miniature Micro Hydro Power Center (MHPC) is a learning media development designed to improve critical thinking skills in elementary science education. The operation of this miniature resembles that of the actual MHPC Karekan, located in Banjarnegara, Indonesia. This study aimed to develop the MHPC Miniature media, evaluate its validity, and test its effectiveness in enhancing students' critical thinking skills. This research employed the Research and Development (R&D) method, using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The research stages included an assessment of teacher and student needs, followed by product validation by material experts (one science lecturer and five experienced teachers), technicians, and nine practitioners. To test its effectiveness, 102 fifth-grade students from the Ki Hajar Dewantara Cluster in North Purwokerto District were selected as the research sample. The sample was divided into an experimental and a control group using a cluster sampling technique. Data from the posttest were analysed for normality and homogeneity before an Independent-Samples T-Test. The results indicated that validation by science experts and practitioners yielded a Content Validity Index (CVI) of > 0.85, indicating the media is highly suitable for learning. Furthermore, the Independent Samples T-test showed that the experimental group using the MHPC miniature performed significantly better than the control group, which used only video-based media (ρ < 0.05). In conclusion, the developed MHPC miniature is a valid and effective tool for fostering critical thinking skills in elementary science learning. These findings imply that integrating contextualized miniatures into the science curriculum can bridge the gap between abstract concepts and real-world applications, providing a scalable model for innovative STEM education.